Processo de constituição da identidade profissional de professores da educação escolar de uma unidade prisional de Minas Gerais - DUARTE, Alisson José Oliveira (2017)
This research inquired whether the teaching experience to imprisoned students, in the context of a prison system school in the Brazilian state of Minas Gerais, could influence teachers’ process of professional identity constitution. Even though schooling in prisons is not a recent fact in the history of the Brazilian prison system institutions, this is still among the areas most neglected and marginalized by public policies and post-secondary education, mainly when we consider the teaching professional. The justification for this research is the need to foment studies that offer reflective and theoretical support concerning the prison system schooling and, above all, in relation to the identity constitution of teachers who work in this very specific field of educational reality. The methodological option for the development of this research is the qualitative model, which uses field inquiry and theoretical references to reach the proposed objectives. The research had as its voluntary participants five teachers who work in a prison system school and the principal of the same institution. Therefore, we used as data collecting instruments: open interviews (audio recorded) and field diaries. The qualitative material obtained during the interviews with the teachers was firstly submitted to the theme content analysis technique. After that, the results obtained in the first procedure were critically crossed and complemented with the information obtained through the interview with the school principal and the observations registered on the field diary, using the data triangulation method. The results demonstrate that the singularities found in the field of the prison system school researched by us can transform significantly the professional identity of teachers who work in this reality, considering that their (institutional, social, moral and ethical) specificities are different from the traditional challenges in non-prison system institutionalized schools. By trying to respond to the general objective of this research, we highlight, based on the methodological procedures of data analysis, three themes of analysis that surround the process of teachers’ professional identity constitution in the prison system school researched by us. In the first theme, “Relationship teacher/student”, we describe how the direct relationship with the imprisoned student can influence the manner the teacher constitutes his or her self-image, self-esteem and professional fulfillment. In the second theme, “Identity for the other and incomprehension feeling”, we emphasize how teachers feel underappreciated and marginalized in relation to the social representation generated by the media and people who do not know the teaching work in prison system schools. In the third theme, “Specificities of teacher’s profile”, we emphasize how the elements and the specificities of teacher’s practice in the micro-universe of prisons can imprint over the teachers’ professional identity qualities and experiences that frequently are not observed in other schooling institutions, which make them become professionals with characteristics and peculiarities in the Young Adults Education. In a society in which minorities are still silenced by the media, by the anonymity, historical prejudices and lack of freedom of speech, we seek in this research to give voice to the teachers involved in the schooling in prisons of this unit, emphasizing the importance and responsibility of university and public education policies to invest in an educational reform, including teachers and their knowledge in order to construct new and democratic models of teaching within prisons, where there is still an old oppressive logic and totalitarian from the beginning of prison.